Inter-sector Inter-Region Model for Russian Economy: Methodology and Application - Suslov, Nikita; Buzulutskov, Vladimir; Isupova, Ekaterina (International Journal of Energy Economics and Policy, 2022)
The paper presented is intended to analyze an approach to a long-term inter-sector and inter-regional economic analysis as based on an optimization model. This approach was developed in IEIE SB RAS and resulted in several directions of application. One of them is investigation of interactions between a national economy and its energy production segment. The model being discussed includes input-output tables for six regions of Russian economy supplemented with model blocks for interregional transportations. It includes a natural block of energy production, processing and transportation. The last version of this model combines 45 products of different economic sectors including 8 ones of an energy sector (rough oil, gas and coal, two kinds of petroleum products, coal processing, electricity and heat), and 6 Russian macro-regions; it is a composition of two sub-models for 2 time periods: 2008-2020 and 2021-2030. Each of the sub-models treats time changes in simplified manner – it means that all the variables are defined for the last year of the period and the variables of the basic year are fixed as exogenous ones. The dynamics of investments into fixed capital is treated as non-linear functions being adapted with the help of linearization techniques.